Lamentations and Hopes of Conflict Victims in Sayyidi Ar-Rais Song (Michael Riffaterre Semiotic Analysis) - Arifina, Nur Dina (Jurnal Theologia, 2023)
This article aims to analyse the lyrics of an Arabic song entitled Sayyidi ar-Rais by Heba Meshary Hamada using Michael Riffaterre's semiotic theory. The song tells about the conflict between Israel and Palestine. The Israeli- Palestinian conflict that has caught the world's attention, through this song Heba M.H wants to convey a message which is her self-expression of the phenomenon that is happening. She tries to describe the situation and condition of the Palestinian people during the conflict. By using Michael Riffaterre's semiotic theory, the researcher wants to dig deeper into the meanings contained in the lyrics of the song Sayyidi ar-Rais. This research is a qualitative-descriptive research with the type of library research where the data obtained comes from literary sources related to the material objects and formal objects used. Based on the results of an analysis of the lyrics of the song Sayyidi ar-Rais using Michael Riffaterre's semiotic theory, namely through heuristic and hermeneutic reading, it was found that the song Sayyidi ar-Rais describes the lamentation of a Palestinian child who tells of the suffering he and the Palestinian people are experiencing as a result of the conflict with Israel, and hopes for freedom and peace for the land of Palestine and also for its people.